Comparative Analysis of Early Clinical Features and Complications of Different Types of Acute Pancreatitis. (25th June 2022) - Wu, Hongsheng; Ma, Keqiang; Liao, Biling; Ji, Tengfei; Zhang, Shengmin; Cao, Tiansheng
Abstract : Background . Acute pancreatitis (AP) is a common surgical acute abdomen. Different kinds of pancreatitis may have different pathophysiological characteristics each other. The objective of this research was to investigate the early clinical features and complications of different types of acute pancreatitis. Methods . 787 AP patients admitted in the Huadu District People's Hospital of Guangzhou during January 2009 and December 2019 were analyzed retrospectively. Among 787 AP patients, 520 (66.1%) were biliary AP (group I), 69 (8.7%) were alcoholic AP (group II), and 198 (25.2%) were hypertriglyceridemic AP (group III). According to the local and systemic complications and mortality in the early stage, we compared and analyzed the clinical characteristics and prognosis of different types of pancreatitis. Results . Mild acute pancreatitis accounted for the highest proportion (79.4%) in group I, while moderately severe acute pancreatitis in group II (36.2%) and severe acute pancreatitis in group III (62.6%). In terms of severity score of the pancreatitis, the average scores of BISAP, Ranson, APACHE-II, and MCTSI of the patients in group III were the highest (p < 0.01 ). The incidence of acute peripancreatic fluid collection and infectious pancreatic necrosis was the highest in group III. The incidences of acute necrotic collection, pancreatic pseudocyst, and walled-off necrosis in group III were significantly higher than those in the other two groups (p < 0.01 ). The incidences of systemic inflammatory response syndrome, sepsis, multiple organ failure, intra-abdominal hypertension, and mortality were highest in group III. Conclusions . There is an upward trend of the incidence rate of hypertriglyceridemic AP in recent years; it has been gradually developed into the second type of acute pancreatitis which is second only to the acute biliary pancreatitis. It is worthy to pay more and more attentions to it due to the feature of its younger onset, high incidence of complications, and high mortality.